POLA PEMAHAMAN KEAGAMAAN MASYARAKAT SIMPANG EMPAT PASAMAN BARAT (Studi Terhadap Aliran Haqqul Yaqin Tarekat Naqsabandiyah) - Sawaluddin Siregar (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
Haqqul Yaqin Tarekat Naqsabandiyah is one of the tarekat that developed in Simpang Empat Pasaman Barat, in spreading sufistism, it uses remembering Methode (dzikir)as a form of ritual and  its teaching. The purpose of ritual activities is to get grace, mercy, pleasure and get the assistance in the world and hereafter, also get the special excess ( such as, magic and treatment), then also hopefulness to achieve closeness with Allah as the ultimate goal. If it is considered, Haqqul Yaqin Tarekat naqsabandiyah has similarity with tarekat muktabarah, it can see based on the theory,  basic teaching and also doing the syariat based on Al-Qur’an and Sunnah also Qaul Ulama.  However, in some case haqqul Yaqin Tarekat Naqsabandiyah is different with Muktabarah tarekat, such as, it’s about the acceptance of new students, wirid, training, tawajjuh and tends to spritual welfare and individual’s supernatural power.